The financial determinants of corporate cash holdings: evidence from growing firms - Gomes, Marília de Sena (2015)
Submitted by Joana Lopes Dias (jdias@ubi.pt) on 2015-01-26T12:54:49Z No. of bitstreams: 1 Tese Marília.pdf: 540977 bytes, checksum: 7138622aa87f9498c4ae7ad76e4fcd01 (MD5)